2007
DOI: 10.1021/bm700687x
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Porphyrins to Tubulin Heterodimers

Abstract: We have investigated the binding of two porphyrins, meso-tetrakis ( p-sulfonatophenyl) porphyrin (TSPP) and protoporphyrin IX (PPIX), to tubulin alpha,beta-heterodimers. TSPP had been shown to directly target microtubules in cells. A comparative study between TSPP and PPIX was carried out because the latter is used in clinical applications and is hydrophobic, in comparison with the water soluble TSPP. The results presented in this manuscript show that both porphyrins bind tubulin with nearly identical stoichio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
47
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 25 publications
(55 citation statements)
references
References 70 publications
7
47
1
Order By: Relevance
“…This is consistent with non-covalent complexation between the dye and the protein through electrostatic interactions between one or more of the four negatively charged SO À 3 groups in TSPP and positively charged residues in the tubulin dimer [25] with the addition of the possible rotation of the phenyl rings in-plane with the porphyrins macrocycle. Conversely, the absorption of tubulin does not appear to change upon binding of TSPP.…”
Section: Absorptionsupporting
confidence: 76%
See 4 more Smart Citations
“…This is consistent with non-covalent complexation between the dye and the protein through electrostatic interactions between one or more of the four negatively charged SO À 3 groups in TSPP and positively charged residues in the tubulin dimer [25] with the addition of the possible rotation of the phenyl rings in-plane with the porphyrins macrocycle. Conversely, the absorption of tubulin does not appear to change upon binding of TSPP.…”
Section: Absorptionsupporting
confidence: 76%
“…We confirmed that addition of tubulin to TSPP results in a $7 nm red shift associated with hypochromicity of the peak of the porphryin ( Figure 1A) [25]. This is consistent with non-covalent complexation between the dye and the protein through electrostatic interactions between one or more of the four negatively charged SO À 3 groups in TSPP and positively charged residues in the tubulin dimer [25] with the addition of the possible rotation of the phenyl rings in-plane with the porphyrins macrocycle.…”
Section: Absorptionsupporting
confidence: 72%
See 3 more Smart Citations